223k views
2 votes
Simplify the expression cos x cot x+ sin x please select the best answer from the choices provided a.0, b.csc x, c. Tan x, d sec x

1 Answer

4 votes

Answer:


cot x = (cos x)/(sin x)


cos x (cos x)/(sin x) + sin x


(cos^2 x)/(sin x) +sin x


sin^2 x + cos^2 x =1

Solving for
cos^2 x we got
cos^2 x =1 -sin^2 x and replacing this we got:


(1-sin^2 x)/(sin x) +sin x


(1)/(sin x) -(sin^2 x)/(sin x) +sin x


csc x -sin x + sin x = csc x

And then the best option for this case would be:

b.csc x

Explanation:

For this case we have the following expression given:


cos x cot x + sin x

We know from math properties that the definition for cot is
cot x = (cos x)/(sin x)

If we use this definition we got:


cos x (cos x)/(sin x) + sin x


(cos^2 x)/(sin x) +sin x

Now we can use the following identity:


sin^2 x + cos^2 x =1

Solving for
cos^2 x we got
cos^2 x =1 -sin^2 x and replacing this we got:


(1-sin^2 x)/(sin x) +sin x


(1)/(sin x) -(sin^2 x)/(sin x) +sin x


csc x -sin x + sin x = csc x

And then the best option for this case would be:

b.csc x

User Rowena
by
4.5k points